Festa, fé e devoção: a formação musical na Igreja de Nossa Senhora da Conceição - Medeiros, Pedro Henrique Simões de (2018)
This dissertation contemplates the musical formation through the religious musical practices of the church of Nossa Senhora da Conceição, located in João Pessoa – PB in the Conjunto Anatólia neighborhood. The purpose of this central dissertation is to understand, discuss and reflect on the conceptions, situations, processes and strategies of music formation that characterize sociocultural practices at the church mentioned above. In addition, verify trough the investigative process: the situations in which the music is present, the processes and strategies of the practices of formation in this context, how are conceived the different dimensions of music training, and the signs that give sense to the music and the formative processes deriving from them. To achieve these objectives, a bibliographical research was developed by the use of literature related to the musical practices of the religious context. Moreover, was made a documentary research through normative documents of the Catholic’s church musical practice and was accessed the official social media of this church. Additionally, were made observations, interviews, recordings and participations at the church’s musical practices. The data of this research were constantly related to the epistemic bases. These bases are divided into two pillars: the first one focus on informal musical education, and the second on studies of musical formation in religious realities. Through these bases was possible to conduct the discussion, reflection, interpretation, analysis and understanding of the musical formation practiced at the church of Nossa Senhora da Conceição. Thus, conclude that the musical formation inserted in the musical practices is being developed by processes of enculturation, imitation, performance, and among others, directly linked to religion. These processes do not occur in isolation, instead they are relating at all times, as well as the contextual musical religious meanings/conceptions. The situations that these processes happen are the ceremonies, the “quermesses” (fundraising events), the rehearsals and meetings. Through these processes and situations it is possible to observe how music is maintained and the signs within the church of Nossa Senhora da Conceição. Thus, can say that through the meaningfull relationship between man and music the phenomenon of musical formation happens. Therefore, this musical formation acts on the maintenance of the sociocultural reality and the practices of this religious context.